Антибиотики и глюкокортикоиды в клинике - Егорова Лидия Ивановна (Медицина, 1978)
Экземпляры: КХ (20161213) / Инвентарный номер: 683792 / Цена: 1.60 / Сис.шифр: 615.9 / Авт.знак: Е 30 / ГРНТИ: 76 / ББК: 5